Geothermal study at the Wenchuan earthquake Fault Scientific Drilling project-hole 1 (WFSD-1): Borehole temperature, thermal conductivity, and well log data. (1st March 2016) - Zheng, Yong; Li, Haibing; Gong, Zheng
Highlights: The thermal conductivity shows correlations with other geophysical properties. The thermal conductivities show significant low anomalies in the main fault zone. The non-uniform vertical fracturing was observed from the temperature logging. The heat flow transition is probably related to the regional tectonic evolution. Abstract: The Wenchuan earthquake Fault Scientific Drilling project-hole 1 (WFSD-1) offers a unique opportunity for studying the faulting behavior and the thermal regime of the Longmen Shan fault zone (LMFZ), east margin of Tibetan Plateau. Thermal conductivity of fault rocks within main fault zone shows strong negative interrelations with the porosity, the gamma ray and the P-wave slowness, as well as a positive interrelation with the density. Here we attribute these correlations to the fractures and the rock-fluid reaction generated from the earthquake, which will increase the porosity, the radioactivity and the P-wave slowness as well as decrease the density and the thermal conductivity, synchronously. 15 continuous temperature profiles were summarized in this paper. Based on integrated studies of temperature variations and thermal gradients, local temperature anomalies were detected at three depth ranges of 480–510 m, 580–610 m and 625–755 m, respectively. These anomalies seem to correspond to different fracture zones and may be attributed to fluid flow in the fractures. In addition, the non-uniform vertical distribution of these temperature anomalies was observed across the co-seismic slip surface at 589.2 m. In the below ∼200 m borehole depth, a prominent thermal anomaly zone was developed, implying more factures were generated in the footwall than the hanging wall during the Wenchuan earthquake. The heat flow ranges from 69 mW/m 2 to 72 mW/m 2 for different logs. The persistence of elevated heat flow in the LMFZ appears to rule out frictional heating on the Yingxiu-Beichuan fault (YBF) as the source of the WFSD-1 value, but is probably related to the regional tectonic evolution.